Infective pericarditis in Nigerian children. - Jaiyesimi, F (1979)
53 children with infective pericarditis were seen at the University College Hospital, Ibadan, between 1967 and 1976. Their ages ranged from 10 days to 15 years but 53% of them were aged 5 years and below. Cough, fever, and breathlessness were the most common symptoms; cardiac decompensation was evident in over 30% of them, 23% had muffled heart sounds, but a pericardial friction rub was audible in only one. The main pathogens identified were Mycobacterium tuberculosis (11 cases), Staphylococcus aureus (11 cases), Escherichia coli (4 cases), Pneumococcus and Pseudomonas (3 cases each). Most of the patients had some other associated infection--such as, bronchopneumonia (12 cases), empyema thoracis (10 cases), lung abscess (10 cases), septicaemis (6 cases), and osteomyelitis (3 cases). Errors in diagnosis were common, the diagnosis having been missed in 72% of the cases identified at necropsy. Even if the correct diagnosis had been made during life and appropriate treatment given, the mortality rate (36%) was high. It is suggested that the onset of cardiac failure in any child with bronchopneumonia, empyema, or lung abscess should always arouse a suspicion of infective pericarditis.